Motor skills of preschooler - Wawryków, Agata; Stecko, Monika; Korabiusz, Katarzyna; Fabian-Danielewska, Anna; Harasimowicz, Joanna; Maciejewska, Martyna; Janik-Fuks, Inga (Journal of Education, Health and Sport, 2019)
The human motoriness is the whole of behaviors, possibilities and needs movement differently manifested at every stage of life. The pre-school period is the so-called golden period of motoriness. At this stage of life, all movement skills that affect further development of the child are improved, both in the physical, mental, intelectual and social spheres. External interventions to improve and improve skills in small and large motor skills seem to be extremely important. We should hold on the occurrence of motor development disorders and the introduction of rehabilitation as soon as possible.